The Role of Akidah Akhlak Teachers in Shaping Students’ Ecological Awareness: A Qualitative Study Based on Religious Ecopedagogy - Fatimah Azzahra; Laily Masruroh (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to analyze the role of Akidah Akhlak teachers in shaping students’ ecological awareness, to identify the forms of ecological awareness developed among students, and to examine how the integration of religious values and instructional practices contributes to environmental character formation within Islamic education. This study employs a qualitative case study design to explore the phenomenon in depth within a natural educational setting. Data were collected through classroom observations, in-depth interviews with key stakeholders including teachers, school leaders, and students, and documentation of institutional programs and learning activities. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, supported by thematic analysis to identify recurring patterns. Data validity was ensured through triangulation techniques and member checking. The findings reveal that students’ ecological awareness is effectively developed through the integration of theological values into learning processes, supported by teacher role modeling, habituation practices, and institutional programs. Teachers function not only as knowledge transmitters but also as moral and spiritual guides who translate religious teachings into concrete environmental practices. Students’ ecological awareness is manifested through the integration of cognitive understanding, affective attitudes, and behavioral actions, as reflected in their active participation in environmental programs such as waste management, greening activities, and sustainable practices. The study also identifies challenges related to inconsistent behavioral habits among some students, which are addressed through reinforcement strategies combining intrinsic and extrinsic motivation. This study introduces the concept of religious ecopedagogy as an integrative framework that combines Islamic theological values with experiential environmental education. It highlights the role of theological habituation in transforming ecological awareness from conceptual understanding into lived behavior, offering a new perspective that bridges religious education and environmental sustainability. Theoretically, this study contributes to the development of an integrative model that connects cognitive, affective, and psychomotor dimensions within the framework of Islamic education and environmental pedagogy. Practically, it provides insights for educators and educational institutions in designing value-based and experience-oriented learning strategies to foster sustainable ecological character. The findings also offer a reference for developing holistic educational policies that integrate religious values with environmental awareness in addressing global ecological challenges.